2019
DOI: 10.1177/1098612x19843214
|View full text |Cite
|
Sign up to set email alerts
|

Acute hindlimb lameness in a 6-month-old cat

Abstract: Clinical presentation: A 6-month-old female spayed domestic shorthair cat was presented for investigation of acute right hindlimb lameness and paresis. What is your diagnosis? Readers are encouraged to review the case history and consider what their diagnostic suspicion is. Also what is the preferred treatment for this injury? And what is the primary cause of this injury?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…9,10 Femoral head and neck ostectomy is currently the most widely reported and performed salvage procedure for feline FCPF. 1,[11][12][13] Studies regarding the outcome of femoral head and neck ostectomy in cats report good-to-excellent medium-to-long-term outcomes based on owners' experience. [14][15][16] However, more objective studies reported muscle atrophy and decreased ground reaction forces in cats after femoral head and neck osteoctomy.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Femoral head and neck ostectomy is currently the most widely reported and performed salvage procedure for feline FCPF. 1,[11][12][13] Studies regarding the outcome of femoral head and neck ostectomy in cats report good-to-excellent medium-to-long-term outcomes based on owners' experience. [14][15][16] However, more objective studies reported muscle atrophy and decreased ground reaction forces in cats after femoral head and neck osteoctomy.…”
Section: Introductionmentioning
confidence: 99%
“…These typically occur secondarily to physeal dysplasia and metaphyseal disorders, with a higher incidence in overweight, male, neutered cats and in certain breeds of pedigree cat. 30,[35][36][37][38][39][40][41][42] They can usually be identified by the lack of a history of trauma, often progressive clinical signs, a potential for bilateral lesions and signalment. Two pathological entities are described.…”
Section: Proximal Physeal Fractures and Femoral Neck Fracturesmentioning
confidence: 99%
“…The treatment of this condition in cats often involves femoral head and neck ostectomy (FHO) (Berzon et al, 1980;Borak et al, 2017;Grayton et al, 2014;Nappier et al, 2019;Rahal et al, 2016). However, a recent study revealed long-term residual gait abnormalities after using this technique (Schnabl-Feichter et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that FCPFs in cats can also occur outside of traumatic circumstances, such as physeal dysplasia (or slipped femoral capital epiphysis), and seem to involve different pathophysiological characteristics than those of dogs (Borak et al ., 2017; Craig, 2001; DeCamp et al ., 1989; Gibson et al ., 1991; Lafuente, 2011; McNicholas et al ., 2002; Queen et al ., 1998). The treatment of this condition in cats often involves femoral head and neck ostectomy (FHO) (Berzon et al ., 1980; Borak et al ., 2017; Grayton et al ., 2014; Nappier et al ., 2019; Rahal et al ., 2016). However, a recent study revealed long‐term residual gait abnormalities after using this technique (Schnabl‐Feichter et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%